Construction of dual active sites for efficient alkaline hydrogen evolution: single-metal-atoms supported on BC2N monolayers. Issue 47 (29th November 2022) - Kong, Weichao; Xu, Jing; Tong, Yanfu; Ding, Yanping; Wang, Jiajun; Li, Bingyu; Wei, Xing; Zhao, Lianming
Abstract : Ni@BC2 N shows an excellent electrocatalytic performance towards the hydrogen evolution reaction in alkaline media. Abstract : Electrocatalytic water splitting suffers from sluggish kinetics towards the hydrogen evolution reaction (HER). Balancing the adsorption/desorption ability towards H* and OH* is considered to be an efficient way to enhance the HER efficiency, but it is too hard at one activity site. In this work, the HER activity of the single 3d transition metal atom-anchored BC2 N monolayer (M@BC2 N, M = Fe, Co, and Ni) was investigated by a density functional theory approach. Our calculation suggests that an efficient dual-active site is formed on M@BC2 N towards the HER, i.e., the metal center M as the OH* active site and its adjacent C atoms as the H* active site. The combination of single M atoms with the BC2 N monolayer can effectively tune the electronic structure of dual active sites to optimize the adsorption of H* and OH*, resulting in a HER activity sequence of Fe@BC2 N < Co@BC2 N < Ni@BC2 N. Notably, the HER exchange current density of Ni@BC2 N reaches up to 0.53 mA cm −2, which is close to the value for commercial Pt/C, suggesting its huge potential in the HER.